STUDY OF DETERMINATION OF THE MODULUS OF ELASTICITY OF FIBER-REINFORCED COMPOSITE USING ULTRASONIC PITCH & CATCH - Agung Priambodo, Toni
The modulus of elasticity in fiber-reinforced composite materials is one of the properties that can function as a diagnostic indicator for alterations in the constituent material, the presence of defects, or the occurrence of material degradation. The determination of the modulus of elasticity using ultrasonic methods has been conducted previously. However, challenges remain, such as the inability to perform in-situ measurements and difficulties in curved materials and large surface materials. The purpose of this research is to investigate the determination of the modulus of elasticity in fiber-reinforced composite materials using the ultrasonic pitch & catch method and to evaluate its capability of differentiating the modulus of elasticity based on variations in fiber architecture, fiber orientation, and fiber volume fraction. The ultrasonic pitch & catch method for determining the modulus of elasticity was validated on steel and aluminum. The determination of the modulus of elasticity in fiber-reinforced composite materials using the ultrasonic pitch & catch method was performed with variations in fiber architecture, fiber orientation, and fiber volume fraction. The test results were compared to tensile testing and classical laminate theory. This research shows the ultrasonic pitch & catch method can be used to obtain the modulus of elasticity in aluminum, steel, and fiber-reinforced composites. Determining the modulus of elasticity in fiber-reinforced composite materials using the ultrasonic pitch & catch method resulted in errors that depended on the fiber preform: 3-42% for unidirectional fiber, 16-36% for woven fiber, and 1-17% for random fiber. The ultrasonic pitch & catch method also demonstrated effectiveness in distinguishing the modulus of elasticity in glass fiber-reinforced composite materials with variations in fiber architecture, fiber orientation, and fiber volume fraction